2008
DOI: 10.1016/j.jmb.2008.06.085
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Kv1.2 and Paddle Chimera Kv Channels in Planar Lipid Bilayers

Abstract: SummaryVoltage-dependent K + channels play key roles in shaping electrical signaling in both excitable as well as non-excitable cells. These channels open and close in response to the voltage changes across the cell membrane. Many studies have been carried out in order to understand the voltage sensing mechanism. Our laboratory recently determined the atomic structures of a mammalian voltagedependent K + channel Kv1.2 and a mutant of Kv1.2 named the 'paddle-chimera' channel, in which the voltage sensor paddle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 30 publications
2
50
0
Order By: Relevance
“…However, the positions and orientations of the S4 arginine residues in these structures vary substantially (15)(16)(17)(18)(19). Electrophysiological studies have shown that membrane-embedded voltage-gated potassium channel from Aeropyrum pernix (KvAP), Kv2.1, and voltage-gated sodium channel from Aerobacter butzleri (NavAb) held at 0 mV become inactivated over time (17,22,24). Therefore, the X-ray structures of these three channels, if completely physiological, should all reflect the inactivated states (state I), not necessarily the states to which they were assigned.…”
Section: Masaomentioning
confidence: 99%
“…However, the positions and orientations of the S4 arginine residues in these structures vary substantially (15)(16)(17)(18)(19). Electrophysiological studies have shown that membrane-embedded voltage-gated potassium channel from Aeropyrum pernix (KvAP), Kv2.1, and voltage-gated sodium channel from Aerobacter butzleri (NavAb) held at 0 mV become inactivated over time (17,22,24). Therefore, the X-ray structures of these three channels, if completely physiological, should all reflect the inactivated states (state I), not necessarily the states to which they were assigned.…”
Section: Masaomentioning
confidence: 99%
“…Paddle chimera protein (␣ and ␤1 subunits) was expressed, purified and reconstituted as described in ref. 15.…”
Section: Methodsmentioning
confidence: 99%
“…1 actually represent the very same channels functioning in different membranes. The Kv channel is called ''paddle chimera,'' a Kv1.2 channel with a voltage sensor paddle from Kv2.1 (14,15). The properties of rapid activation, inactivation, a negative midpoint voltage and sensitivity to VSTx1 are observed when the channels are reconstituted into planar bilayers consisting of the lipids 1-palmitoyl-2-oleoyl-glycero-3-phosphoethanolamine (POPE) and 1-palmitoyl-2-oleoyl-glycero-3-phospho-1-glycerol (POPG) in a 3:1 ratio.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, our previous measurements of hERG did not result in any observations of the expected temporal or voltage dependent conductance of ion channel ensembles,{Portonovo et al 2013#34} similar to others' measurements, {Zhang et al 2012 #38} although Oshima and coworkers reported voltage dependent single channel conductance. {Oshima et al 2013 #33} Temporal and voltage dependence of conductance for purified ion channels reconstituted in lipid bilayers has been previously reported by Tao and MacKinnon (Tao and MacKinnon 2008) and Schmidt and MacKinnon (Schmidt et al 2009) for K v 1.2 and K v AP channels, respectively. In the work described here, we used droplet bilayers to measure ion channel currents from membrane preparations of hERG-expressing cells at the single channel and ensemble levels, demonstrating ion selectivity and dose-dependent inhibition by E-4031 and dofetilide, with IC 50 values of 17 nM and 9.65 μM.…”
Section: Introductionmentioning
confidence: 94%